Response to orphaning in two Neotropical termites: Armitermes euamignathus and Embiratermes festivellus - Costa-Leonardo, Ana Maria [UNESP]; Soares, Helena Xavier [UNESP]; Barsotti, Raquel Cristina [UNESP] (Wiley, 1998)
In this paper we examine the potential of the termites Armitermes euamignathus Silvestri: 1901 and Embiratermes festivellus (Silvestri, 1901) (Isoptera, Termitidae, Nasutitermitinae) to produce neotenics experimentally. Three nests of the mound-building termite A. euamignathus, from the Brazilian cerrado, had their primary queens removed in August 1994. After 12 months, only one mound survived; it had a normal appearance. In this healthy, orphaned colony we found the primary king, six physogastric nymphoid female replacement reproductives, two ergatoid female replacement reproductives, 46 nymphs, several presoldiers, soldiers, workers, larvae and many eggs. These data show that neotenics in A. euamignathus may originate from both workers and nymphs, but nymphoids are produced in larger numbers. The biometric study of nymphs and nymphoids suggests that these brachypterous neotenics were derived from third instar nymphs after a single moult or from four instar nymphs after a reduction of wing bud length. A piece of an E. festivellus nest with some third instar nymphs, soldiers and workers was kept under laboratory conditions. After 12 months, the whole experimental subcolony was examined and appeared to contain two pigmented nymphoid females, two pigmented nymphoid males, only one larva, seven nymphs of the same instar, 148 workers, five soldiers and many eggs. These results also indicate the capacity of the termite E. festivellus to produce nymphoid neotenics. These neotenic females were laying eggs, but they were not physogastric after a year, unlike some nymphoids of the same species collected from natural colonies.
Keywords: Armitermes; Embiratermes; Isoptera; Neotenics; Nymphoid reproductives; Replacement reproductives; Termitidae; colony; community response; queen; removal experiment; termite; Armitermes euamignathus; Embiratermes festivellus